The first species of Trichopsomyia Williston, 1888 (Diptera: Syrphidae) described from the Oriental region, with a discussion on the character states of the pilosity of the katepisternum - van Steenis, Jeroen; Wyatt, Nigel P. (European Journal of Taxonomy, 2020)
The first Oriental species of the genus Trichopsomyia Williston, 1888, Trichopsomyia pilosa sp. nov. (Java), has been discovered and is now described. This Oriental species of Trichopsomyia has several characters strongly differing from the other species within this genus. It is hypothesized that it forms a separate group within Trichopsomyia. One species, Trichopsomyia formiciphila Downes, Skevington & Thompson, 2017, from Australia, is similar to the Oriental species described here, and the group is named after this first described species, hence the formiciphila group. The characters for a future phylogenetic analysis are discussed. The character states of the pilosity of the katepisternum and the shape of the metasternum hitherto used in a phylogenetic analysis of Syrphidae Latreille, 1802 are discussed too.